On the Usefulness of Earnings and Earnings Research: Lessons and Directions from Two Decades of Empirical Research - Lev, Baruch (Journal of Accounting Research, 1989)
Baruch Lev, On the Usefulness of Earnings and Earnings Research: Lessons and Directions from Two Decades of Empirical Research, Journal of Accounting Research, Vol. 27, Current Studies on The Information Content of Accounting Earnings (1989), pp. 153-192